Adaptability in Socio-Political Contexts: Moving Beyond Ability and Intelligence - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
It is increasingly difficult to be a popular political or corporate leader. Public and employee expectations are evolving quickly and technologies now impose constant demands on 'engagement'. While most leaders are already expected to possess both the skills and the smarts to navigate within highly complex environments, what sets the good apart from the mediocre is an ability and willingness to exert the necessary efforts for change. 'Adaptability', however, requires an appreciation of the psychological processes underlying human cognition, emotion and behaviours, said a distinguished line-up of speakers at the inaugural Behavioural Sciences Institute Conference 2012.